Gaya Bahasa Rocky Gerung pada Masa Kampanye Pemilu Presiden 2019 dalam Acara Indonesia Lawyers Club - Roma Fiorentina; Auzar Auzar; Mangatur Mangatur (Journal on Education, 2023)
This research was conducted to find out the language style used by Rocky Gerung during the 2019 presidential elestion campaign at the Indonesia Lawyers Club event. This type of research is qualitative with descriptive analysis method. Data collection techniques are carried out by observing and recording techniques. The data source was obtained from the video of the Indonesia Lawyers Club event. After the data is obtained, the data is analyzed based on the type of language style. The style of language that tends to be dominant in this study is the style of affirmation which consists of interruptions, corrections, repetitions, rhetoric, stigmatism, and tautology. As a political observer, Rocky Gerung is known for his assertive speaking style, daring to criticize and often using satirical language in his speeches. In this research, the style of language Rocky used the most was interrupt with the aim of emphasizing the meaning of what he said.